Study of solar powered cooling technologies for Singapore : photovoltaic vs. solar thermal using TRNSYS - Teo, Benjamin How Wei (2014)
In context of air-conditioning, Singapore is one of the countries with the highest building energy consumption throughout the world. A reduction on energy consumption by air-conditioning unit and improve energy efficiency is needed. Solar Powered Cooling Technologies was introduced as an alternative air-conditioning system. A comparison between Solar Thermal Absorption system and Photovoltaic Vapour Compression system is needed to determine which system is suitable to run in Singapore. The Solar Powered Cooling systems were required to generate cooling for a space with a floor area of 460.8m2. Using TRNSYS simulation tool, the necessary components for both systems were connected with the required parameters. From the simulation, Solar Thermal Absorption system generates a cooling load between 88kW to 90kW on a typical day. Photovoltaic Vapour Compression system generates a constant cooling load of 81.57kW with a longer duration. Photovoltaic Vapour Compression system provides a solar fraction of 58.7% while Solar Thermal Absorption system has about 31.8%. About 37.5% of solar energy is loss in the Photovoltaic Vapour Compression system as compared to Solar Thermal Absorption system with a loss of 15%. On a typical week, Solar Thermal system shows more variation in cooling load and solar fraction than the Photovoltaic system. Comparing the systems with the cooling load required for a year, Photovoltaic Vapour Compression system covers 14.2% more than Solar Thermal Absorption system. With the ROI for Photovoltaic Vapour Compression system is lower, the rate of return by the saving cost estimated will be able to hit the installation cost earlier. In conclusion, with the results from TRNSYS simulation and cost analysis, Photovoltaic Vapour Compression system would be feasible as the Solar Powered Cooling system for Singapore.